A systematic review of economic policy uncertainty and sustainable development goals: climate action center - Mohamad, Arifha; Afsheen, Saima; Rashid, Umi Kartini; Zakaria, Mohd Rezuwan Shah; Megat Zambri, Wan Anis Aqilah (2024)
This study investigates the relationship between Economic Policy Uncertainty (EPU) and Sustainable Development Goals (SDGs), with a specific focus on SDG 13 addressing climate change. The introduction highlights global concerns regarding emissions, economic expansion, and natural resource depletion, emphasizing the importance of the SDGs, particularly SDG 13. The study focuses to Malaysia, exploring its commitment to international climate agreements, including the National Policy on Climate Change and its adaptation efforts. The Malaysian Development of SDG section examines the involvement of Malaysian companies in the UN Global Compact, highlighting their contributions to sustainability. The economic, social, and environmental aspects of SDGs in Malaysia are discussed, emphasizing the country's transformation into an upper-middle-income economy and its progress in poverty eradication, healthcare, and climate resilience. Various studies on the intersection of SDGs and social work, corporate financial performance, energy efficiency, and poverty distribution in Malaysia are presented. In summary, this study contributes to the limited but growing body of literature on the intersection of EPU and SDGs. It calls for further research across different nations to formulate appropriate policies that align with sustainable development objectives. The study recommends future research to conduct pre and post analyses of carbon emission trading in relation to EPU and climate change action